Strategy for Developing Lecturer Professionalism in Facing the Challenges of Distance Education in the Digital Era - Kadarisman, Kadarisman; Ridwan, Taufik; Prasasti, Ian Harum; Hakim, Arif Rohman; Fahmi, Muhammad (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2024)
Developments have opened the door to teaching without geographic boundaries, allowing students to access learning materials from anywhere, even in remote areas. This impacts demands for adaptation of teaching strategies and encourages the development of professionalism in lecturers who not only master technological aspects but also comprehensively understand the dynamics of distance education. Educational technology is essential in changing and improving education in this digital era. This research aims to identify strategies for developing lecturer professionalism in facing distance education challenges in the digital era. This type of research is qualitative research. Data collection techniques include interviews and observations of lecturer and student respondents at Al-Ihya Kuningan Islamic University—research results from strategies for developing professionalism in facing educational challenges in the digital era. To be more effective, you can apply several methods: mastery of technology and digital platforms, development of relevant and interactive learning materials, effective online communication skills, and time management skills. By implementing this strategy, lecturers can develop professionalism in facing distance education challenges in the digital era to provide a quality learning experience for students.